Kesesuaian hasil pengukuran Low Density Lipoprotein Cholesterol menggunakan persamaan Friedewald, Hopkins, dan Homogeneous Enzymatic Colorimetric Assay di RSUP Sanglah, Bali, Indonesia - I Made Dharma Pramana; Ida Ayu Putri Wirawati; Ni Nyoman Mahartini (DiscoverSys Inc., 2021)
Background: LDL-C concentration can be obtained by calculation from equations and measurement methods. There are many LDL-C equations, but the most commonly used is the Friedewald equation, and the most recent is the Hopkins equation. This study aims to determine LDL-C measurements' agreement using the Friedewald equation, Hopkins equation, and homogeneous enzymatic colorimetric assay.Methods: This was a cross-sectional study, from January-February 2020, with 570 samples LDL-C examination results by Friedewald equation, Hopkins equation, and homogeneous enzymatic colorimetric assay divided into 3 groups based on TG levels. Data were analyzed by SPSS version 17 for Windows.Results: Spearman correlation test found a near-perfect correlation between LDL-C using Friedewald and Hopkins equations to direct examinations with values r =0.921 and r =0.907. Limit of agreement from the Bland-Altman test shows an average of >90% for both equations with direct measurements. Mann-Whitney test showed a significant difference between LDL-C direct measurement and Friedewald equation in Total Group, TG 200-400 mg/dL and TG> 400 mg/dL while for Hopkins equation only in TG group> 400 mg/dL (p<0.05). Based on Total Allowable Error (TAE) analysis, LDL-C from Hopkins equation in TG group 200-400 mg/dL appears to be superior to the Friedewald equation.Conclusion: Friedewald equation and Hopkins equation give good concordance at TG levels <200 mg/dL while at triglyceride levels 200-400 mg/dL Hopkins equation gives better concordance than the Friedewald equation. At triglyceride levels,> 400 mg/dL Friedewald and Hopkins equations show low accuracy, so it is recommended to use the direct method. Latar Belakang: Konsentrasi low density lipoprotein cholesterol (LDL-C) dapat diperoleh dengan 2 cara yaitu menggunakan perhitungan dengan persamaan dan metode pengukuran langsung (direct). Banyak persamaan perhitungan LDL-C tetapi yang paling umum digunakan adalah persamaan Friedewald dan yang terbaru adalah persamaan Hopkins. Penelitian ini bertujuan untuk mengetahui kesesuaian hasil pengukuran LDL-C menggunakan persamaan Friedewald, persamaan Hopkins dan homogeneous enzymatic colorimetric assayMetode: Penelitian menggunakan rancangan analitik potong lintang dari bulan Januari-Pebruari 2020 dengan 570 sampel hasil pemeriksaan LDL-C dengan persamaan Friedewald, persamaan Hopkins dan homogeneous enzymatic colorimetric assay yang dibagi 3 kelompok berdasarkan kadar trigliserida (TG). Data dianalisis dengan SPSS versi 17 untuk Windows.Hasil: Uji statistik Spearman didapatkan korelasi mendekati sempurna antara LDL-C menggunakan persamaan Friedewald dan Hopkins terhadap pemeriksaan direct dengan nilai r=0,921 dan r=0,907. Limit of agreement dari uji Bland-Altman menunjukkan rata-rata > 90% untuk kedua persamaan dengan pengukuran direct. Uji Mann-Whitney menunjukkan perbedaan bermakna antara LDL-C pengukuran direct dengan persamaan Friedewald pada Kelompok Total, TG 200-400 mg/dL dan TG >400 mg/dL sedangkan untuk persamaan Hopkins perbedaan hasil yang bermakna hanya pada kelompok TG >400 mg/dL (p<0,05). Berdasarkan analisis Total Allowable Error (TAE), LDL-C persamaan Hopkins pada kelompok TG 200-400 mg/dL lebih unggul dari persamaan Friedewald.Kesimpulan: Persamaan Friedewald dan persamaan Hopkins memberikan kesesuaian yang baik pada kadar TG <200 mg/dL sedangkan pada kadar trigliserida 200-400 mg/dL, persamaan Hopkins memberikan kesesuaian yang lebih baik daripada persamaan Friedewald. Pada kadar TG >400mg/dL persamaan Friedewald dan Hopkins menunjukkan akurasi yang rendah sehingga disarankan untuk menggunakan metode direct.